A Scientometric Analysis of Highly Cited Papers of Pakistan in COVID-19 Research 2020-2023 - Gupta, Brij Mohan; Dhawan, Surinder Mohan; Singh, Yogendra; Srivastava, Nupur; Vaishya, Raju; Kappi, Mallikarjun; Nabeesab Mamdapur, Ghouse Modin (Journal of Data Science, Informetrics, and Citation Studies)
Highly Cited Papers (HCPs) are influential sources of information that highlight trend-setting areas of research and identify key players within a subject. This study aims to measure the research performance of Pakistan in COVID-19-related research from 2020 to 2023, focusing specifically on HCPs that have received more than 100 citations. A bibliometric approach was employed to analyse COVID-19 research papers from Pakistan, with data sourced from Scopus. The period covered was from 2020 to 2023. The analysis included metrics such as the number of HCPs, citation counts, international collaboration, and funding sources. A total of 7602 COVID-19-related papers were published by Pakistani researchers, of which 164 (1.59%) were classified as HCPs. These HCPs collectively registered 38,244 citations, averaging 233.10 citations per paper. International collaboration was evident in 81.71% of these HCPs, and 32.92% were funded by external agencies. The USA, China, UK, and Saudi Arabia were identified as the leading international collaborating partners. Despite the high collaboration rates, the average productivity per organization in Pakistan was low, with only 6.32 HCPs per organization. Similarly, the average productivity of 31 research authors was 2.48 HCPs per author. International collaboration has positioned Pakistan at the centre stage in COVID-19 research, with external funding significantly enhancing research quality. However, the share of HCPs remains less than 2% of Pakistan's total COVID-19-related publications, indicating a significant gap between the quantity and quality of research output. This suggests that while Pakistan has made notable contributions, there remains substantial potential for addressing the ongoing health challenges posed by COVID-19 through enhanced research efforts.
Keywords: COVID-19; Research; Citation; Collaboration; Pakistan.